2011
DOI: 10.1007/s10803-010-1170-0
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Sensitivity to Sad Facial Expressions in High Functioning Autism Spectrum Disorders is Associated with Symptomatology and Adaptive Functioning

Abstract: Prior studies implicate facial emotion recognition (FER) difficulties among individuals with autism spectrum disorders (ASD); however, many investigations focus on FER accuracy alone and few examine ecological validity through links with everyday functioning. We compared FER accuracy and perceptual sensitivity (from neutral to full expression) between 42 adolescents with high functioning (IQ>80) ASD and 31 typically developing adolescents (matched on age, IQ, sex ratio) across six basic emotions and examined l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
89
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 62 publications
21
89
1
Order By: Relevance
“…higher expression intensity). This result points towards diminished recognition sensitivity, in line with Wallace et al (2011) who found diminished sensitivity in ASD compared to controls over the six basic emotions combined. Since motion perception performance decreases more in ASD compared to controls when viewing times are short (Robertson et al, 2014) and facial expressions are dynamic and fleeting, impaired motion perception (literature review by Dakin & Frith, 2005) could manifest in confusions of emotional facial expressions as neutral, especially at the low intensity level where movements are of small magnitude.…”
Section: Discussionsupporting
confidence: 83%
“…higher expression intensity). This result points towards diminished recognition sensitivity, in line with Wallace et al (2011) who found diminished sensitivity in ASD compared to controls over the six basic emotions combined. Since motion perception performance decreases more in ASD compared to controls when viewing times are short (Robertson et al, 2014) and facial expressions are dynamic and fleeting, impaired motion perception (literature review by Dakin & Frith, 2005) could manifest in confusions of emotional facial expressions as neutral, especially at the low intensity level where movements are of small magnitude.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have found people with ASD to be impaired on tasks assessing their knowledge of other people's mental states while sparing other perceptual and cognitive abilities (for review, see Baron-Cohen 1995). In addition, previous studies have observed clear emotion recognition deficits in people with ASD (compared with TD participants) in tasks tapping into more complex sociocognitive abilities by instructing the participants to recognize/identify more subtle emotional expressions (Humphreys et al 2007;Wallace et al 2011). Consistent with these studies, the current ultra-rapid social categorization task also requires participants to integrate different sources of perceptual information by using a more ecologically valid and developmentally appropriate paradigm (BaronCohen et al 2001).…”
Section: Goal 2: Social Perception In Asdsupporting
confidence: 63%
“…These studies yielded mixed results (e.g., Ashwin, Wheelwright, & BaronCohen, 2006;Corden, Chilvers, & Skuse, 2008;Kennedy & Adolphs, 2012;Wallace et al, 2011). From these lines of research and theorizing, it seems to be difficult to make strong predictions regarding uniqueness of individual differences based on the available literature.…”
Section: The Emotion Category Specificity In Facial Expression Percepmentioning
confidence: 99%